Exosomes Derived from Human Amniotic Fluid Mesenchymal Stem Cells Preserve Microglia and Neuron Cells from Aβ - Manuela Zavatti (International Journal of Molecular Sciences, 2022)
Background: Neuroinflammation is involved in neuronal cell death that occurs in neurodegenerative diseases such as Alzheimer’s disease (AD). Microglia play important roles in regulating the brain amyloid beta (Aβ) levels, so immunomodulatory properties exerted by mesenchymal stem cells may be exploited to treat this pathology. The evidence suggests that the mechanism of action of human amniotic fluid stem cells (hAFSCs) is through their secretome, which includes exosomes (exo). Methods: We examined the effect of exosomes derived from human amniotic fluid stem cells (hAFSCs-exo) on activated BV-2 microglia cells by lipopolysaccharide (LPS) as a neuroinflammation model. To investigate the exo effect on the interplay between AD neurons and microglia, SH-SY5Y neuroblastoma cells treated with Aβ were exposed to a conditioned medium (CM) obtained from activated BV-2 or co-culture systems. Results: We found that the upregulation of the markers of pro-inflammatory microglia was prevented when exposed to hAFSC-exo whereas the markers of the anti-inflammatory macrophage phenotype were not affected. Interestingly, the hAFSC-exo pretreatment significantly inhibited the oxidative stress rise and apoptosis occurring in the neurons in presence of both microglia and Aβ. Conclusion: We demonstrated that hAFSC-exo mitigated an inflammatory injury caused by microglia and significantly recovered the neurotoxicity, suggesting that hAFSC-exo may be a potential therapeutic agent for inflammation-related neurological conditions, including AD.